Review of porous adsorbents for the separation of nitrogen from natural gas - Nandanwar, Sachin U.; Corbin, David R.; Shiflett, Mark B. (Industrial & Engineering Chemistry Research, 2020)
Natural gas is one of the critical fossil fuel sources in the world to fulfill current energy demand in the global market. Methane is the primary component in natural gas and its concentration is dependent on the source; a variety of impurities, such as nitrogen, carbon dioxide, oxygen, helium, hydrogen sulfide, water, and heavier hydrocarbons can be present, which reduces the overall fuel quality. Purification of natural gas is important in order to meet the U.S. pipeline and minimum heating value specifications. The separation of nitrogen from methane is challenging because of their similar molecular size (i.e., the two gases differ in kinetic diameter by only 0.16 angstrom). This Review discusses different methods for separating nitrogen from methane. Of these methods, pressure swing adsorption is one of the most effective techniques for separating nitrogen from natural gas using porous adsorbents, and encouraging results have been demonstrated in the past few decades. Many types of porous adsorbents are discussed here, including carbon molecular sieves, activated carbons, zeolites, titanosilicates, and metal-organic frameworks. Future trends and materials are discussed to put into perspective the new opportunities in this research area.

Review on selective production of acetophenone from oxidation of ethylbenzene over heterogeneous catalysts in a decade - Nandanwar, Sachin U.; Rathod, Simmy; Bansal, Videsha; Bokade, Vijay V. (Catalysis Letters, 2021)
The consumption of acetophenone (AP) is increasing worldwide because of its applications in products such as alcohol, aldehydes, resins, esters, fragrances, and pharmaceuticals. AP is manufactured via several methods like decomposition of cumene hydroperoxide, Hock process, and Friedel-Crafts acylation reaction using homogeneous catalysts with solvent and oxidant. However, it causes several environmental problems that deteriorate the production of AP with these methods. Oxidation of ethylbenzene (EB) is one of the promising methods to synthesize AP in liquid and vapor phases reaction using heterogeneous catalysts, which plays a vital role for selective production of AP. In this review, numerous heterogeneous catalysts are discussed including transition metal nanoparticles, transition metal complexes, and metal free catalysts (carbon nanotubes) used in last 10 years for oxidation of EB. Additionally, catalyst activity along with reaction parameters and its effect, mechanisms, and kinetics study are summarized in this article. The future scope of this reaction is also highlighted. Moreover, this work identifies best catalysts for bulk production of AP with high yield to satisfy global requirement.
Keywords: acetophenone; ethylbenzene; Heterogeneous catalysts; Oxidation reaction; reaction mechanisms